Evaluación de la calidad de energía eléctrica en instalaciones fotovoltáicos conectadas a la red de bajo voltaje - Pilatasig Montaluisa, Alexander Danilo (2015)
With the growing development of electric energy through renewable generation, this paper aims to make the study of the quality of electricity that produces a photovoltaic system connected to the network in a building (SFCR). Theoretical and practical research is done, for which performance data from an actual facility, equipped with meters located power quality at the point of common connection between the grid and the (SFCR), are analyzed. Quality parameters obtained with those defined in the applicable national and international regulations are contrasted. Finally, mitigation measures are investigated to improve quality indices deficit.